Kompres Air Hangat dalam Mengurangi Nyeri Persalinan Kala I - Marlynda Happy Nurmalita Sari; Anis Alina Ramadhani (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
Every prespective mother has different intensity and level of pain during a labor. The greatest pain happens in the end of the first phase on servix opening, contraction and maximum uterus. Labor pain causes an uncomfortable feeling during labor process. There are many ways to resolve the pain, but the most effective way have not found yet. The purpose of this research is to measure the warm water compresses efectivity in resolving labor pain on the first phase. Design research with quasi experiment. The sample of this research are 28 giving birth mothers on the first active phase. The study was conducted by compressing warm water on the mother's back for 20 minutes by measuring pain scale. The results showed that mothers who entered labor in the first active phase had pain with a mean of 3.28 higher than mothers after warm water compresses with a mean of 1.54. The results of the dependent T-test analysis is P-value 0.0001 (P <0.05). There is a significant difference in pain of mothers entering labor on the first active phase before being given warm water compresses than after being given warm water compresses.